REVIEW EUROPEAN SECURITY ARCHITECTURE: AN IMPERFECT AND UNFINISHED SYSTEM (Journal of the Spanish Institute for Strategic Studies, 2018)
Since the end of the Cold War, the role that Europe plays in the world has undergonea complete transformation. The creation of the European Union andits meteoric growth during the period discussed in this book, with the rapidincorporation of states to the initial seed of the European Economic Community, hasbeen a complex process. A reality was created and with it the need to establish a commonsecurity architecture in order to preserve said reality – something that has turnedinto a difficult exercise when faced with the need to meet the interests of the directlyinvolved players: the states.